2021
DOI: 10.1097/jcma.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

The biological function and diagnostic value of miR-762 in nasopharyngeal carcinoma

Abstract: METHODS Clinical specimensPlasma samples were collected from 106 patients with pathological diagnosis of NPC and 51 healthy volunteers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In prior research, miR-762 has been found to regulate a range of target genes in different contexts. The upregulation of miR-762 in non-small cell lung cancer, bladder cancer, breast cancer, and nasopharyngeal carcinoma has been linked to enhanced tumor cell invasivity, migration, and proliferation [ 39 42 ]. However, there have been no prior studies regarding the role of this specific miRNA in keratinocytes or endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, miR-762 has been found to regulate a range of target genes in different contexts. The upregulation of miR-762 in non-small cell lung cancer, bladder cancer, breast cancer, and nasopharyngeal carcinoma has been linked to enhanced tumor cell invasivity, migration, and proliferation [ 39 42 ]. However, there have been no prior studies regarding the role of this specific miRNA in keratinocytes or endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of miR‐762 has been explored in various cancers. In nasopharyngeal carcinoma, upregulation of miR‐762 was suggested to associate with progression by promoting tumor cells' proliferation and invasion 22 . The miR‐762 has been reported to involve in the circRNA‐miRNA‐mRNA network in lung cancer as diagnostic or prognostic factor 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal carcinoma, upregulation of miR-762 was suggested to associate with progression by promoting tumor cells' proliferation and invasion. 22 The miR-762 has been reported to involve in the circRNA-miRNA-mRNA network in lung cancer as diagnostic or prognostic factor. 23,24 Although the underlying links between SLE/NPSLE and various cancers remain unclear, it's no doubt that immune dysfunction is the common ground of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, miR-762 has been found to regulate a range of target genes in different contexts. The upregulation of miR-762 in non-small cell lung cancer, bladder cancer, breast cancer and nasopharyngeal carcinoma has been linked to enhanced tumor cell invasivity, migration, and proliferation [30][31][32][33]. However, there have been no prior studies regarding the role of this speci c miRNA in keratinocytes or endothelial cells.…”
Section: Discussionmentioning
confidence: 99%